The impact of crowds on visibility in emergency department: Integrating agent-based simulation and space syntax analysis - Hao Yuan; Ying Zhou (Frontiers of Architectural Research)
Emergency departments (EDs) are among the busiest hospital units, where visibility is crucial for surveillance, collaboration, and wayfinding. In China, high ED patient volumes lead to crowded corridors, significantly impacting visibility. However, current visibility assessment methods focus on static obstructions such as walls and columns, neglecting crowd obstruction, and underestimating visual impediments.To address this research gap, this study proposes a novel visibility assessment method combining agent-based simulation and space syntax analysis. Based on peak-hour behavioral data from Hospital R's ED, crowd movement was simulated across six ED plans with different corridor layouts. The simulated crowd positions were then treated as visual obstacles, and space syntax theory was applied to evaluate visibility under crowd obstruction at various timesteps. The findings reveal that: 1) ring corridor layouts reduce patient backtracking and corridor congestion; 2) ring corridor layouts facilitate better natural surveillance of the overall space by medical staff with crowd obstruction considered; 3) ring corridor layouts enable medical staff to see each other more easily, supporting team collaboration, regardless of crowd obstruction; 4) simple layouts perform best in terms of wayfinding, irrespective of crowd obstruction. This study presents the first comprehensive quantitative assessment of ED visibility under crowd obstruction, with potential applications in other crowded public spaces.